Muscle Pain: Diagnosis and Treatment - Mense, Siegfried; Gerwin, Robert D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The companion volume to Muscle Pain: Understanding the Mechanisms, this text shifts the emphasis from concepts to practical advice. It facilitates the diagnosis and management of the often enigmatic symptoms of chronic muscle pain and includes the combined expertise of leaders in the field who have contributed cutting-edge material on the major syndromes. As a set, this volume and its partner are essential reading for practitioners treating acute and chronic pain conditions involving muscle tissues.
Myofascial Pain Syndrome -- Myofascial Pain Syndrome -- Morphology of Myofascial Trigger Points: What Does a Trigger Point Look Like? -- Fibromyalgia Syndrome -- Fibromyalgia Syndrome: Clinical Aspects and Management -- Gender, Genetics, and Other Risk Factors Increasing Vulnerability to Fibromyalgia -- Other Muscle Pain Syndromes -- Low Back Pain of Muscular Origin -- Masticatory Muscle Pain -- Inflammatory Myopathies -- Whiplash Injury, Muscle Pain and Motor Dysfunction -- Brain Imaging of Muscle Pain.
Keywords: Medicine; Human physiology; Neurosciences; Toxicology; Anesthesiology; Neurology; Rheumatology; Biomedicine; Neurosciences; Human Physiology; Neurology; Pharmacology/Toxicology.; Anesthesiology; Rheumatology